Development of a RPA-CRISPR/Cas12a based rapid visual detection assay for Porcine Parvovirus 7 - Wen, Shubo; She, Lemuge; Dang, Sheng; Liao, Ao; Li, Xiaorui; Zhang, Shuai; Song, Yang; Li, Xiangyang; Zhai, Jingbo (Frontiers in Veterinary Science, 2024)
IntroductionPorcine Parvovirus (PPV) is a significant pathogen in the pig industry, with eight genotypes, including PPV7, identified since its emergence in 2016. Co-infections with viruses such as Porcine Circovirus 2 (PCV2) and Porcine Reproductive and Respiratory Syndrome Virus (PRRSV) pose serious risks to swine health. Thus, there is an urgent need for rapid, sensitive, and specific detection methods suitable for use in field settings or laboratories with limited resources.MethodsWe developed a CRISPR/Cas12a-based assay combined with recombinase polymerase amplification (RPA) for the rapid detection of PPV7. Specific RPA primers and five CRISPR RNAs (crRNAs) were designed to target a highly conserved region within the NS1 gene of PPV7. Optimization of crRNA and single-stranded DNA (ssDNA) concentrations was performed to enhance the assay’s performance.ResultsCrRNA optimization identified crRNA-05 as the optimal candidate for Cas12a-based detection of PPV7, as all synthesized crRNAs demonstrated similar performance. The optimal crRNA concentration was determined to be 200 nM, yielding consistent results across tested concentrations. For ssDNA optimization, the strongest fluorescence signal was achieved with 500 nM of the FAM-BHQ ssDNA receptor. The assay showed a minimal detection limit of 100copies/μl for PPV7, confirmed through fluorescence and lateral flow detection methods. Specificity testing indicated that only PPV7 DNA samples returned positive results, confirming the assay’s accuracy. In tests of 50 lung tissue samples from diseased pigs, the RPA-Cas12a assay identified 29 positive samples (58%), surpassing the 22 positive samples (44%) detected by conventional PCR. This highlights the RPA-Cas12a method’s enhanced detection capability and its potential utility in clinical surveillance and management of PPV7 in swine populations.DiscussionThe RPA-Cas12a assay effectively detects PPV7 in clinical samples, enhancing disease surveillance and control in pigs. Its adaptability to resource-limited settings significantly improves PPV7 management and prevention strategies, thereby supporting the overall health and development of the pig industry.